Effectiveness of a Flipped Classrooms on Mathematical Innovative Development, Students’ Achievement in Mathematics among Female from Grade Eleventh in Scientific Stream - Qunaibi, Abeer Rushdi; Ikhlayel, Ghanem Yousef (Journal of Curriculum and Teaching Methodology, 2022)
This Study was designed to investigate the effects of flipped classroom model on mathematical innovative development, student achievement and motivation towards learning mathematics among female from grade (11) scientific stream at Wedad Naser Deen Secondary School. The quasi-experimental method was used. The sample consisted of (40) female students divided into two groups; the experimental group and the control group. The study instruments were observation achievement test in “sequences and series” in mathematics. The results of the study showed that students enjoyed learning with the flipped classroom. In addition, there were differences between the students of the experimental group and control group in achievement test, mathematical innovation and motivation towards learning mathematics of the experimental group. Also, the results showed an existence of greater positive relation between the dependent variables (students’ achievement, mathematical innovative). The study recommended to encourage teachers to use flipped classroom strategy and adopting it in teaching. In addition, Preparing courses and workshops for teachers and students and training them on the activities and educational methods related to flipped classroom.